The Position of the University in the Infrastructure, Which Supports Technological Entrepreneurship - R. A. Zayakina (Высшее образование в России, 2023)
The article’s goal is to eliminate the contradiction between the need for university activities to support and develop technological entrepreneurship and the lack of a sequence of steps leading to the achievement of the desired result. This contradiction is proposed to be resolved by identifying the position of the university in the infrastructure supporting technological entrepreneurship.The paper highlights three main infrastructural positions of the university, called “Supplier of Talents”, “Platform of Academic Technological Entrepreneurship” and “Technological Entrepreneurial Hub”. The first focuses on the development of creative thinking of students seeking to develop high-tech products and support their entrepreneurial intentions. The second focuses on the achievements of university researchers, based on which promising high-tech start-ups are launched and profitable small innovative enterprises are developed. The third relies on mediation and facilitation to coordinate communications between key parties for promoting high-tech business. In this position, the university is an access point to the main success factors of a technological entrepreneurial project. It is more than others capable of stimulating the economic development of the region.One university can hold several positions. Each of the listed positions is endowed with functional characteristics corresponding to their purpose and performs the tasks assigned to them. Starting from an infrastructural position close to the university, it becomes possible to clearly define the criteria that the university needs to have to effectively fulfill these tasks. And the presence of criteria makes it possible to identify dominant problems, adapt university resources, and bring social practices and educational technologies into line.